Desain User Interface Website Pemetaan Tanaman Obat Dan Langka Di Kabupaten Kediri Dengan Menggunakan Figma - Adhi Wicak Milbar Gamas; Anita Sari Wardani; Rina Firliana; M Najibuloh Muzzaki; Sucipto; M Iqbal Khalid; Shandy Arshad Busro Cahyono; Heru Stiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The potential of medicinal and rare plants in Kediri Regency is quite large with the supportive topography of the area. However, information about these rare and medicinal plants is not widely known by the general public. The Kediri Regency Government (Balitbangda – Regional Research and Development Agency) is collaborating with Nusantara University PGRI to develop a website for mapping medicinal and rare plants in Kediri Regency. To realize the mapping website, it is necessary to design a user interface from a prototype website for mapping medicinal and rare plants. The design of the prototype uses the design thinking method. This research produces a website prototype for mapping medicinal and rare plants. The results of user assessments of the website prototype design show that 30% rate it very well, 46% rate it good, 21% rate it quite well and 3% rate it less well